Highly efficient air-stable/hysteresis-free flexible inverted-type planar perovskite and organic solar cells employing a small molecular organic hole transporting material. (November 2017) - Reddy, Saripally Sudhaker; Shin, Sungmin; Aryal, Um Kanta; Nishikubo, Ryosuke; Saeki, Akinori; Song, Myungkwan; Jin, Sung-Ho
Abstract: To acknowledge exceptionally productive flexible perovskite solar cells, low-temperature-processable efficient organic hole transporting materials are very significant for the emerging photovoltaic research. A new organic small molecular hole transporting material ( N -(4-(9 H -carbazol-9-yl)phenyl)-7-(4-(bis(4-methoxyphenyl)amino)phenyl)- N -(7-(4-(bis(4-methoxyphenyl)amino)phenyl)-9, 9-dioctyl-9 H -fluoren-2-yl)-9, 9-dioctyl-9 H -fluoren-2-amine (CzPAF-TPA)) has been rationally designed and synthesized for both highly efficient solution-processed flexible and rigid inverted-type planar heterojunction perovskite solar cells (i-PSCs) and flexible and rigid bulk heterojunction inverted organic solar cells (BHJ IOSCs). The dopant-free CzPAF-TPA-based device displayed significantly improved device performance in solution-processed flexible i-PSCs and flexible BHJ IOSCs with power conversion efficiencies (PCEs) of 12.46% and 7.52%, respectively, with negligible hysteresis, which is superior to that of standard HTM. Furthermore, the high PCE was recorded on rigid ITO substrate in dopant-free i-PSCs (PCE ~ 15.71%) and BHJ IOSCs (PCE ~ 8.74%). Notably, the promising technique of flash-photolysis time-resolved microwave conductivity was also well correlated with the obtained results. In addition to their high device performance in flexible as well as rigid i-PSCs and flexible BHJ IOSCs, they also showed long-term stability over 500 h and 30 days with minimal loss of initial performance. Graphical abstract: Highlights: A new small molecular organic hole transporting material (HTM) is reported. Utilized for dopant-free flexible/rigid inverted perovskite solar cells (i-PSCs). Used in flexible/rigid bulk heterojunction (BHJ) inverted organic solar cells (IOSCs). New HTM-based devices exhibit superior, hysteresis-free device performance. They also showed excellent long-term stability in flexible/rigid i-PSCs and BHJ IOSCs.